Students' English Proficiency, Perceptual Learning Style Preference and Second Language Tolerance of Ambiguity - Mohd Rawian, Rafizah (2002)
The purpose of this study was to examine students' English proficiency, perceptual learning style preference and tolerance of ambiguity. A total of 314 respondents were randomly sampled from four secondary schools in the District of Hulu Langat. A descriptive correlational study was utilised and the theoretical framework of the study was based on several models of learning. The Perceptual Learning Style Preference Questionnaire was used to investigate respondents' perceptual learning style preference. This questionnaire categorised the students into auditory, kinesthetic, tactile and visual learners. The Second Language Tolerance of Ambiguity Scale was used to measure respondents' levels of ambiguity tolerance. English proficiency was evaluated based on respondents' PMRE nglish grades. Frequency distribution, independent t test and Pearson correlation test were used to analyse the data. The study found that the male and female students had chosen the kinesthetic learning style as a major learning style while the tactile and the visual learning styles were selected as minor learning styles. However, there was a difference in the auditory learning style preference because the females had regarded this learning style as a major learning style while the males had considered it as a minor style. The Malays, Chinese and Indians had selected the kinesthetic learning style as a major learning style and regarded the tactile and visual learning styles as minor styles. The auditory learning style was a major style for the Indians but it was considered as a minor learning style for the Malays and Chinese. The Malays had stronger preference in tactile learning style and the Chinese were found to h ave stronger preference in visual learning style. The Indians on the other hand had stronger preference in auditory learning style.